Evaluating the Therapeutic Impact of Exercise on Chronic Diseases: A Comprehensive Review and Future Directions - Liu Ai Dong (Ilmu Inovasi Nusantara, 2024)
This study aims to evaluate the therapeutic benefits of exercise interventions for chronic diseases, including cardiovascular diseases, hypertension, diabetes, and cancer. The research involves a comprehensive analysis of the scope, application, and challenges associated with various exercise therapy programs, providing valuable insights for clinical practice and future research. Data were sourced from the WHO website, Web of Science, and several databases, such as PubMed, Embase, CNKI, Wipu, Zhi.com, and Wanfang, employing keywords like